Impact of big data and analytics on quality management in rural tourism in southern Africa - Zimbabwe: A systematic literature review - Njodzi Ranganai; Vitalis Basera; Tendai Shelton Muwani (School of Tourism, Universitas Ciputra Surabaya, 2023)
Big data and analytics have assumed a significant role in the technological advancement that is shaping the world's travel industry today, posing both significant challenges and opportunities for rural tourism in southern Africa. Big data and analytics provide useful information to all tourism businesses, allowing them to estimate visitor need, optimize decision-making, knowledge exchanges and relationships with consumers, and deliver the best service in a more productive and effective way, thereby managing quality. The focus of this research is to investigate the problems and opportunities that may arise from the use of big data and analytics in rural tourism, its management, and the sector's future. The research content was obtained from popular web sources including articles indexed in Google Scholar, institutional repositories, dissertations and Scopus. Thirty-one peer reviewed articles published between 2012 and 2022 were considered for review. A thread of the problems and opportunities faced by use of big data and analytics was drawn inferring to rural tourism in Zimbabwe, a country in southern part of Africa. Despite widespread privacy and security issues, big data and analytics are widely thought to be advantageous for tourist and hospitality firms as founded in literature. In addition, big data and analytics is offering fresh viewpoints on the quality management discussion to both the tourist and hospitality industries. This study is useful for both scholars and practitioners interested in the utilization of big data and analytics.